VD_FINDINFO Jug / 2011 / 280 vom 20. Mai 2011 - VD Tribunal cantonal (2011)
CONSTATATION DES FAITS, CONTRAINTE SEXUELLE, ACTE D'ORDRE SEXUEL AVEC UN ENFANT | 187 ch. 1 CP, 189 al. 1 CP, 398 al. 3 let. b CPP (CH)